Haptic interaction perception, devices and applications - Kajimoto, Hiroyuki; Ando, Hideyuki; Kyung, Ki-Uk (Springer, 2015)
This book is aimed not only at haptics and human interface researchers, but also at developers and designers from manufacturing corporations and the entertainment industry who are working to change our lives. This publication comprises the proceedings of the first International AsiaHaptics conference, held in Tsukuba, Japan, in 2014. The book describes the state of the art of the diverse haptics- (touch-) related research, including scientific research into haptics perception and illusion, development of haptics devices, and applications for a wide variety of fields such as education, medicine, telecommunication, navigation, and entertainment.